Determinan Pertumbuhan Output Sektor Pertanian Berdasarkan Aspek Ekonomi Dan Lingkungan - Muhamad Syahrul; Zulfa Emalia (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2025)
The agricultural sector faces significant challenges due to climate change, declining arable land, and uncertain investment patterns that affect output growth—particularly in Java and Sumatra, which are key agricultural regions in Indonesia. Moreover, regional disparities, productivity fluctuations, and structural transformation have shifted development priorities toward industrial and service sectors. These challenges are exacerbated by the sector’s high vulnerability to extreme climate events and commodity price instability. Therefore, a deeper understanding of the key determinants of agricultural output is crucial to formulate adaptive and well-targeted policy responses. This study aims to analyze the effects of rice productivity, climate change, and agricultural investment on the agricultural output in Java and Sumatra during the 2018–2022 period. The study uses panel data from 16 provinces and applies panel data regression with the Fixed Effect Model (FEM), selected through Chow and Hausman tests, supported by classical assumption testing and hypothesis testing. The results indicate that climate change has a negative and significant effect on agricultural output, while agricultural investment has a positive and significant effect. Meanwhile, rice productivity shows no significant effect on agricultural output. This study provides important policy implications for developing climate-adaptive agricultural strategies and encouraging investments to promote sustainable growth in the agricultural sector..